2015
DOI: 10.1089/vim.2014.0111
|View full text |Cite
|
Sign up to set email alerts
|

Role of Interferon Gamma and Tumor Necrosis Factor–Related Apoptosis-Inducing Ligand Receptor 1 Single Nucleotide Polymorphism in Natural Clearance and Treatment Response of HCV Infection

Abstract: Hepatitis C virus (HCV) pathogenesis and treatment outcomes are multifactorial phenomena involving both viral and host factors. This study was designed to determine the role of tumor necrosis factor-related apoptosis-inducing ligand receptor 1(TRAIL-R1) and interferon gamma (IFN-γ) genetic mutations in susceptibility and response to interferon-based therapy of hepatitis C virus (HCV) infection. The detection of TRAIL-R1 rs4242392 and IFN-γ rs2069707 single nucleotide polymorphisms was completed in 118 chronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Comparing the distribution of (−764 G/C, rs2069707) alleles between the three groups revealed that the carriage of C allele was significantly higher in SVC than the CHC and control groups, and this was in agreement with the study by Azam et al ., who found that there was a strong association between the IFN‐γ genotype rs2069707GG and the spontaneous clearance of HCV …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Comparing the distribution of (−764 G/C, rs2069707) alleles between the three groups revealed that the carriage of C allele was significantly higher in SVC than the CHC and control groups, and this was in agreement with the study by Azam et al ., who found that there was a strong association between the IFN‐γ genotype rs2069707GG and the spontaneous clearance of HCV …”
Section: Discussionmentioning
confidence: 99%
“…Comparing the distribution of (−764 G/C, rs2069707) alleles between the three groups revealed that the carriage of C allele was significantly higher in SVC than the CHC and control groups, and this was in agreement with the study by Azam et al, who found that there was a strong association between the IFN-γ genotype rs2069707GG and the spontaneous clearance of HCV. 14 Others stated that the −764 G allele was associated with a higher level of IFN-γ than the −764 C allele, and no mutation was detected in the −764 position. 35 Another study reported that the association of the −764 G alleles with spontaneous recovery was not as strong as the association with treatment response.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…TRAIL is expressed as cell surface protein, mostly by activated immune cells such as T and B cells [ 181 ], neutrophils [ 182 , 183 , 184 ], dendritic cells [ 185 ], monocytes and macrophages [ 186 , 187 , 188 , 189 , 190 ], natural killer and NKT cells (NK) [ 191 , 192 , 193 , 194 , 195 , 196 , 197 , 198 , 199 , 200 , 201 ]. TRAIL play a crucial role both during viral clearance [ 202 , 203 , 204 , 205 , 206 , 207 , 208 , 209 , 210 , 211 , 212 , 213 , 214 ] and tumour immune surveillance [ 215 , 216 , 217 , 218 , 219 , 220 ]. Mechanistically, during innate immunity, NK cells and CTLs (cytotoxic T cells) promote apoptosis of target cells, either by releasing soluble factors such as the cytolytic granules [ 184 , 221 , 222 , 223 ], which contain perforin and granzymes, or by engaging membrane-bound death ligands like FasL or TRAIL [ 200 , 221 , 224 , 225 , 226 , 227 ,…”
Section: Physiological and Physiopathological Functions Of Trailmentioning
confidence: 99%